Mental Block Pada Dewasa Awal - yulia, afrina; Rahayu, Sri Putri (Batanang : Jurnal Psikologi, 2023)
Early adulthood is often referred to as a transitional period, which is an episode of an individual's life in adjustment. This phase is often considered the most difficult phase in human development, because an individual usually still depends on their parents, teachers, friends in solving problems. them, but in this early adulthood they are required to be independent. Where as an adult it is hoped that they will be able to solve the problems or difficulties they are experiencing and they will be reluctant to ask questions or just tell others about their problems for fear of being considered immature. Thus I used descriptive literature with a qualitative approach to review several journals and reading sources. It can be concluded that an individual cannot be said to have mental health if the individual is unable to move or the individual has something that is blocking him from moving forward. So it can be concluded that┬á greatly affects the mindset and behavior of individuals in the present and in the future, so it will cause when an individual who has a┬á will experience difficulties in living their life, when they are in the early adult phase they will experience difficulties in solving complex problems, and they will experience difficulties in social relationships let alone relationships that lead to marriage and having new roles in their lives.Keywords: Early Adulthood, Mental Health, Mental Block,Therapy, Mental Block Symptoms